CNS Efficacy of Osimertinib With or Without Chemotherapy in Epidermal Growth Factor Receptor-Mutated Advanced Non-Small-Cell Lung Cancer - Jänne, PA (2024)
PURPOSE We report CNS efficacy of first-line osimertinib plus chemotherapy versus osimertinib monotherapy in patients with epidermal growth factor receptor (EGFR)-mutated advanced non-small-cell lung cancer (NSCLC) from the phase III FLAURA2 study according to baseline CNS metastasis status. Methods Patients were randomly assigned to osimertinib plus platinum-pemetrexed (combination) or osimertinib monotherapy until disease progression or discontinuation. Brain scans were performed in all patients at baseline and progression and at scheduled assessments until progression for patients with baseline CNS metastases; scans were assessed by neuroradiologist CNS blinded independent central review (BICR). Results On the basis of baseline CNS BICR, 118 of 279 (combination) and 104 of 278 (monotherapy) randomly assigned patients had ≥one measurable and/or nonmeasurable CNS lesion and were included in the CNS full analysis set (cFAS); 40 of 118 and 38 of 104 had ≥one measurable target CNS lesion and were included in the post hoc CNS evaluable-for-response set (cEFR). In the cFAS, the hazard ratio (HR) for CNS progression or death was 0.58 (95% CI, 0.33 to 1.01). In patients without baseline CNS metastases, the HR for CNS progression or death was 0.67 (95% CI, 0.43 to 1.04). In the cFAS, CNS objective response rates (ORRs; 95% CI) were 73% (combination; 64 to 81) versus 69% (monotherapy; 59 to 78); 59% versus 43% had CNS complete response (CR). In the cEFR, CNS ORRs (95% CI) were 88% (73 to 96) versus 87% (72 to 96); 48% versus 16% had CNS CR. CONCLUSION Osimertinib plus platinum-pemetrexed demonstrated improved CNS efficacy compared with osimertinib monotherapy, including delaying CNS progression, irrespective of baseline CNS metastasis status. These data support this combination as a new first-line treatment for patients with EGFR-mutated advanced NSCLC, including those with CNS metastases.